2021
DOI: 10.15295/bmij.v9i4.1889
|View full text |Cite
|
Sign up to set email alerts
|

An empirical comparison of stock market bubbles

Abstract: Financial asset bubbles occur due to systematic and continuous differences between fundamental and market values. Due to high growth periods and foreign capital inflows, bubbles are also seen in stock market indexes, especially in emerging market economies. This study analyzes the existence of bubbles in BIST100, IDX COMPOSITE, BOVESPA, MDEX, NIFTY 50, SHANGAI, and S&P 500 stock markets for the period 2009:01-2021:06.  RADF, SADF, and GSADF tests are applied to detect bubbles on stock market closing prices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 22 publications
(29 reference statements)
0
13
0
Order By: Relevance
“…It was depicted a difference between the affinity values of compounds 3 b (−9.4 kcal/mol) and 3 d (−9.1 kcal/mol), which show the best affinity values in vitro studies, and the affinity values of compound 3 c (−10.7 kcal/mol) (Table 6). All amino acid interactions of 3 b and 3 d compounds, which have higher efficiency in vitro studies, with pancreatic lipase were observed the same compared to the standard orlistat for in silico studies [30] . Therefore, from this point of view, it might explainable why pancreatic lipase and compounds 3 b and 3 d have high efficacy in vitro studies.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…It was depicted a difference between the affinity values of compounds 3 b (−9.4 kcal/mol) and 3 d (−9.1 kcal/mol), which show the best affinity values in vitro studies, and the affinity values of compound 3 c (−10.7 kcal/mol) (Table 6). All amino acid interactions of 3 b and 3 d compounds, which have higher efficiency in vitro studies, with pancreatic lipase were observed the same compared to the standard orlistat for in silico studies [30] . Therefore, from this point of view, it might explainable why pancreatic lipase and compounds 3 b and 3 d have high efficacy in vitro studies.…”
Section: Resultsmentioning
confidence: 66%
“…The molecular docking studies for the benzothiazole‐sulfonate hybrid derivatives ( 3 a – i ) was executed in line with protocols previously established [30,48–50] . The target proteins for our docking studies were sourced from the Protein Data Bank.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Compound 5 b was found to have similar interactions with orlistat in terms of bond structure and bond distance. The interactions of compound 5 b with pancreatic lipase were found to be similar compared to orlistat interaction as eleven amino acids [28] . While there were four conventional hydrogen bonds among the bond types formed by Orlistat, compound 5 b did not have conventional hydrogen bonds (Table 2).…”
Section: Resultsmentioning
confidence: 89%
“…The inhibitory effect of benzothiazole‐sulfonate hybrid derivatives containing the azomethine motif ( 5 a – i ) on the pancreatic lipase (PDB ID:1ETH) enzyme was determined by comparison with Orlistat as a standard. While the affinity of orlistat to the enzyme was calculated as −7.1 kcal/mol, [28] the affinity values of the benzothiazole‐sulfonate hybrid derivatives ( 5 a – i ) to the pancreatic lipase enzyme were found as −8.9, −8.7, −8.6, −9.1, −8.7, −8.9, −8.5, −8.8, and −8.6 kcal/mol, respectively. The order of affinity values for all compounds was observed to be 5 d>5 a=5 f>5 h>5 b=5 e>5 c=5 i>5 g>orlistat , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation